2012
DOI: 10.2741/s251
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the hematopoietic cancer niche focus on chronic lymphocytic leukemia

Abstract: Chronic Lymphocytic Leukemia (CLL) is a B cell malignancy characterized by the accumulation of mature monoclonal CD5-positive B cells in the blood, secondary lymphoid tissues, and marrow. The infiltration of CLL cells in lymphoid tissues is a key element of disease pathogenesis. It is in such tissues that are found the microenvironments that provide CLL cells protection from spontaneous and/or drug-induced apoptosis. CLL cells actively shape their microenvironment by producing cytokines and chemokines, and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 114 publications
1
1
0
Order By: Relevance
“…We also examined the motility of CLL-cells co-cultured with marrow mesenchymal stromal cells (MSCs) cultured at a physiologic oxygen tension (e.g., 5% O 2 in N 2 ). Such MSCs secrete CXCL12 or Wnt5a, as described [24, 25]. We found that co-culture with stromal cells enhanced the migration capacity of CLL cells.…”
Section: Resultssupporting
confidence: 74%
“…We also examined the motility of CLL-cells co-cultured with marrow mesenchymal stromal cells (MSCs) cultured at a physiologic oxygen tension (e.g., 5% O 2 in N 2 ). Such MSCs secrete CXCL12 or Wnt5a, as described [24, 25]. We found that co-culture with stromal cells enhanced the migration capacity of CLL cells.…”
Section: Resultssupporting
confidence: 74%
“…Clonal expansion, survival, and proliferation of CLL occur in niches of the lymphoid tissues and the bone marrow. This supportive microenvironment provides contact-dependent stimuli with stromal endothelial cells, nurse-like cells and activated CD4+ T cells expressing CD40 ligand, in addition to an enhanced expression of several chemokines and cytokines that have been reported to regulate survival and proliferation of CLL cells [73][74][75]. This contact-dependent survival effect is partially mediated by miRNAs regulating activity.…”
Section: Involvement Of Tme-associated Mirnas In Proliferation and Sumentioning
confidence: 99%